A gest??o de portf??lio de projetos e o alinhamento estrat??gico de TI - estudo das rela????es considerando o papel da tecnologia - Araujo, Marcos de (2018)
Project Management is one of the means by which organizations implement strategies to achieve success. It is also a fact the evolution and expansion of the use of information technology (IT) resources by organizations in a business reality with a digital focus, characterized by the implementation of projects of this nature. In this context, the strategic alignment of it becomes one of the main objectives of the organizations. Therefore, the aim of this dissertation is to analyze the relationship between project portfolio management and the strategic alignment of it in conjunction with the influence of the intensity of the use of technology. The contribution to the practice presents an analysis of the relationships between project portfolio management and the strategic alignment of it. Through a survey with companies of various sizes and segments, from Brazil and abroad. Data analysis was performed by modeling structural equations by partial minimum squares ??? PLS. The results indicate that the portfolio management of IT projects has a positive relationship with the strategic alignment of it and that the intensity of the use of the technology in the organization, contrary to the expected, does not affect this relationship.